KERANGKA KERJA PENGEMBANGAN ASET PARIWISATA DARI MODEL TRIPLE HELIX Hubungan Akademia-Industri-Pemerintah - A Gima Sugiama (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
The overall purpose of this study was to develop an understanding of the Triple Helix model on tourism services. There are three institutions on Triple Helix: university-industry-government, which each others relate and work together to contribute for tourism development. The study was conducted on the rules of tourism in Indonesia. It was found that the Triple Helix III model is the synergic model for Indonesia tourism development. Each party: Academia-Industry-Government could be contribute to develop tourism assets according to the each capacities and capabilities. The universities, industry and together with government  could be elaborate the synergic discussions, solve the problems, formulate and implement of tourism policies.